Different electrically charged proteins result in diverse bacterial transport behaviors in porous media - D. Wu; He, L.; Ge, Z.; Tong, M.; Kim, H. (Water Research, 2018)
The influence of proteins on bacterial transport and deposition behaviors in quartz sand was examined in both NaCl (10 and 25 mM) and CaCl2 solutions (1.2 and 5 mM). Bovine Serum Albumin (BSA) and bovine trypsin were used to represent negatively and positively charged proteins in natural aquatic systems, respectively. The presence of negatively charged BSA in suspensions increased the transport and decreased bacterial deposition in quartz sand, regardless of the ionic strength and ion types. Whereas, positively charged trypsin inhibited the transport and enhanced bacterial deposition under all experimental conditions. The potential mechanisms controlling the changes of bacterial transport behaviors varied for different charged proteins. The steric repulsion resulting from BSA adsorption onto both bacteria and quartz sand was found to play a dominant role in the transport and deposition of bacteria in porous media with BSA copresent in suspension. BSA adsorption onto bacterial surfaces and competition for deposition sites onto sand surfaces (adsorption of quartz sand surfaces) contributed to the increased cell transport with BSA in suspension. In contrast, the attractive patch-charged interaction induced by the adsorption of trypsin onto both bacteria and quartz sand had great contribution to the decreased bacterial transport in porous media with trypsin copresent in suspension. The increase in bacteria size, and the adsorption of trypsin onto cell surfaces (resulting in less negative cell surface charge) and quartz sand surfaces (providing extra deposition sites) were found to be the main contributors to the decreased transport and increased deposition of bacteria in quartz sand with trypsin in suspension. © 2018
Keywords: " Serum Albumin; Adsorption; animal; Animals; article; Bacteria; Bacteria (microorganisms); Bacteria transport; bacterial growth; bacterial phenomena and functions; Bacterial transport; bacterium; bacterium adherence; Bovinae; bovine; bovine serum albumin; Bovine serum albumins; Bovine" calcium; calcium chloride; Cattle; Cell membranes; cell surface; Cell surface charges; cell suspension; cell transport; chemistry; colloid; competition (ecology); Contrast media; Deposition; electric field; electricity; Escherichia coli; Experimental conditions; experimental study; Ionic strength; macromolecule; Mammals; microbiology; Natural aquatic systems; nonhuman; Osmolar Concentration; osmolarity; Patch-charged interaction; pH; physiology; porosity; Porous materials; porous medium; Positively charged proteins; priority journal; protein; Proteins; Quartz; Sand; silicon dioxide; Site competition; Sodium chloride; Steric interaction; Steric interactions; surface charge; surface property; suspension; Suspensions; transport process; trypsin; Water Microbiology; zeta potential